Ультразвук та його застосування в промисловості - Дідур, В. В.; Петриченко, Є. А.; Новик, Олексій Юлійович; Didur, D.; Petrychenko, I.; Novyk, Oleksii (Запоріжжя : 2023, 2023)
UA: В статті розглянуто питання застосування ультразвуку в різних галузях промисловості. Представлено схеми ультразвукових апаратів. Надано фактори впливу ультразвуку на макуху в матриці маслопресу. Дія ультразвуку на технологічні та хімічні процеси має певний характер: стимулюючий, інтенсифікуючий, оптимізуючий. Ультразвукові коливання мають характерні особливості, що визначають широке використання ультразвуку в техніці і науці. Основні з них: невелика довжина хвилі; відносно невеликий період коливань, що дає можливість випромінювати ультразвукові хвилі імпульсами, також можна проводити в середовищі точний відбір сигналів розповсюдження; при невеликій амплітуді коливання є можливість набуття максимальних значень енергії ультразвуку; ультразвукове поле сприяє суттєвим акустичним витокам (це формує певні ефекти: фізичні, хімічні, біологічні та медичні.); при простому захисті ультразвукових коливань нечутно обслуговуючому персоналу, що не створює дискомфорту. EN: The article discusses the issue of using ultrasound in various industries. Schemes of ultrasonic devices are presented. Factors of influence of ultrasound on the cake in the matrix of the oil press are given. The current state of engineering and technology is focused on the development and implementation of innovative technologies in various technological processes aimed at increasing the efficiency of the industrial sector of the economy. In recent years, ultrasound has begun to play an increasingly important role in various industries. The effect of ultrasound on technological and chemical processes has a certain character: stimulating, when ultrasonic oscillations are the driving force of the investigated process (during dispersion and acoustic cleaning); intensifying, when ultrasonic waves increase the speed of processes (during dissolution and drying, acoustic crystallization); optimizing, when ultrasound regulates the course of the process (in granulation, centrifugation, acoustic pressing). Ultrasonic vibrations have characteristic features that determine the wide use of ultrasound in technology and science. The main ones are: small wavelength; a relatively small oscillation period, which makes it possible to emit ultrasonic waves in pulses, it is also possible to carry out accurate selection of propagation signals in the environment; with a small amplitude of oscillation, there is a possibility of acquiring maximum values of ultrasound energy; the ultrasonic field contributes to significant acoustic leaks (this creates certain effects: physical, chemical, biological and medical); with simple protection, ultrasonic vibrations are inaudible to service personnel, which does not cause discomfort.
Ultrasound and its application in industry
Дідур В. В., Петриченко Є. А., Новик О. Ю. Ультразвук та його застосування в промисловості. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. Запоріжжя : ТДАТУ. 2023. Вип. 13, том 1. C.118-126.
Keywords: ультразвук; коливання; випромінювач; вплив; пресування; ultrasound; oscillations; emitter; impact; pressing